Conservative management and female gender are associated with increased cancer‐specific death in patients with isolated primary urothelial carcinoma in situ. (23rd July 2014) - Alanee, S.; Bauman, J.; Dynda, D.; Frye, T.; Konety, B.; Schwartz, B.
<x xml:space="preserve">Abstract</x> Our goal was to investigate the effect of patient and disease characteristics on the probability of cancer‐specific death (CSD) in cases of isolated urothelial carcinoma in situ (CIS). We performed a retrospective analysis of patients diagnosed with isolated CIS between 1990 and 2010 identified from the Surveillance, Epidemiology, and End Results (SEER) database. Competing risk analysis using Cox proportional hazard model was used to examine the probability of CSD controlling for possible covariates. Overall (n = 1432), patients were mainly male (75%), mean age at diagnosis was 71 years, median survival 47 months, and 65% of the patients had CIS in their upper urinary tract. Caucasians were the predominant race (90%). CIS was the cause of death in 87/1432(6%) of the total cohort; 69/1239 (6%) of patients who underwent surgery, and 18/193 (9%) of the patients who were managed conservatively (CM). On multivariate analysis, CM [hazard ration (HR) = 2.019, CI: 1.189–3.429, P = 0.009] and female gender (HR = 1.690, CI: 1.041–2.741, P = 0.033) were associated with CSD, while age, site, race and year of diagnosis were non‐significant predictors. Female gender and conservative management were positively associated with CSD. Multi‐institutional collaboration is needed to validate markers for poor prognosis in cases of isolated CIS.